Evaluation of a Primary Care-Integrated Mobile Health Intervention to Monitor between-Visit Asthma Symptoms - Sulca Flores, Jorge A.; Dalal, Anuj K.; Sousa, Jessica; Foer, Dinah; Rodriguez, Jorge A.; Plombon, Savanna; Bates, David W.; Arcia, Adriana; Rudin, Robert S. (Applied Clinical Informatics, 2024)
Objectives This study aimed to evaluate implementation of a digital remote symptom monitoring intervention that delivered weekly symptom questionnaires and included the option to receive nurse callbacks via a mobile app for asthma patients in primary care.Methods Research questions were structured by the NASSS (Nonadoption, Abandonment, Scale-up Spread, and Sustainability) framework. Quantitative and qualitative methods assessed scalability of the electronic health record (EHR)-integrated app intervention implemented in a 12-month randomized controlled trial. Data sources included patient asthma control questionnaires; app usage logs; EHRs; and interviews and discussions with patients, primary care providers (PCPs), and nurses.Results We included app usage data from 190 patients and interview data from 21 patients and several clinician participants. Among 190 patients, average questionnaire completion rate was 72.3% and retention was 78.9% (i.e., 150 patients continued to use the app at the end of the trial period). App use was lower among Hispanic and younger patients and those with fewer years of education. Of 1,185 nurse callback requests offered to patients, 33 (2.8%) were requested. Of 84 PCP participants, 14 (16.7%) accessed the patient-reported data in the EHR. Analyses showed that the intervention was appropriate for all levels of asthma control; had no major technical barriers; was desirable and useful for patient treatment; involved achievable tasks for patients; required modest role changes for clinicians; and was a minimal burden on the organization.Conclusion A clinically integrated symptom monitoring intervention has strong potential for sustained adoption. Inequitable adoption remains a concern. PCP use of patient-reported data during visits could improve intervention adoption but may not be required for patient benefits.
Keywords: remote symptom monitoring; electronic health record integration; user-centered design; intervention design; mobile health; digital health implementation; asthma